Synchronous breast and colon cancer: factors determining treatment strategy. (10th July 2013) - Higgins, L; Robertson, I; Khan, W; Barry, K
Abstract : A 67-year-old woman presented with synchronous breast and colonic tumours, in the absence of family history. Following multidisciplinary discussion, the patient was started on endocrine therapy for breast cancer. Initial surgical management consisted of right hemicolectomy together with segmental resection of a serosal deposit adherent to the distal ileum, for a moderately differentiated pT4NO caecal carcinoma. Three months later, right mastectomy and axillary clearance confirmed node positive invasive ductal carcinoma. The original treatment plan was to prioritise adjuvant chemotherapy for breast cancer postmastectomy. However, the subsequent CT finding of an enlarged, suspicious mesenteric lymph node mass on repeat staging raised concern regarding its origin. Image-guided biopsy revealed metastatic colonic adenocarcinoma and the patient was switched to a colon cancer chemotherapy regime. Following adjuvant chemotherapy for colonic carcinoma, an en-bloc surgical resection of the enlarging metastatic nodal mass was performed with clear resection margins. The patient is currently asymptomatic.